(untitled) (The Conference Hub, 2025)
The article discusses the fact that the spiritual and educational image of a people, which is aesthetically formed by its history, values, worldview, and traditions, is the basis of nationality, that nationality is manifested in the unique thinking, lifestyle, and mentality of the people, and that mentality is essentially a spiritual portrait of the people as they are, that this portrait acquires psychological significance through nationality, and that the role and characteristics of national color in fiction are analyzed.